Chromosomally Located fosA7 in Salmonella Isolates From China - Wang, Jing; Wang, Yan; Wang, Zhen-Yu; Wu, Han; Mei, Cai-Yue; Shen, Peng-Cheng; Pan, Zhi-Ming; Jiao, Xinan (Frontiers in Microbiology, 2021)
This study aimed to investigate the prevalence of fosfomycin fosA7 in Salmonella enterica isolates from food animals and retail meat products in China and the impact of fosA7 on bacterial fitness. A total of 360 Salmonella isolates collected from 11 provinces and cities in China were detected for fosA7. All fosA7-positive Salmonella isolates were determined MICs and sequenced by Illumina Hiseq. The fosA7 gene of S. Derby isolate HA2-WA5 was knocked out. The full length of fosA7 was cloned into vector pBR322 and then transformed into various hosts. MICs of fosfomycin, growth curves, stability, and fitness of fosA7 were evaluated. The fosA7 gene was identified in S. Derby (ST40, n=30) and S. Reading (ST1628, n=5). MICs to fosfomycin of 35 fosA7-positive isolates were 1 to 32 mg/L. All fosA7 were located on chromosomes of Salmonella. The deletion of fosA7 in HA2-WA5 decreased fosfomycin MIC by 16-fold, and slightly affected its fitness. The acquisition of plasmid-borne fosA7 enhanced MICs of fosfomycin in Salmonella (1,024-fold) and E. coli (16-fold). The recombinant plasmid pBR322-fosA7 was stable in S. Typhimurium, S. Pullorum, S. Derby and E. coli, except for S. Enteritidis, and barely affected on the growth of them, but significantly increased biological fitness in Salmonella. The spread of specific Salmonella serovars such as S. Derby ST40 will facilitate the dissemination of fosA7. fosA7 can confer high-level fosfomycin resistance and enhance bacterial fitness in Salmonella if transferred on plasmids, thus it has the potential to be a reservoir of mobilized fosfomycin resistance gene.